Development of the Methodology and Mathematical Tools for Strategic Decision-Making Process Modeling of the Digital Business Ecosystem - Vitaly Viktorovich Kuzin; Oksana Yurievna Kirillova; Leonid Alexandrovich Zhigun; Alla Vavilina (Mathematics)
This article presents a methodology of the decision-making process using mathematical tools, which can become a practical tool for decision-makers on the functioning and strategic development of business ecosystems and their components depending on changes in the internal, micro- and macroenvironment. An algorithm for finding linearly independent elements of digital business ecosystems and a new option for interpreting their results are developed. It is proposed that this impact be determined by calculating the eigenvectors of the matrix and identifying the dependence through the contribution of the eigenvectors to the overall mechanism of the system. A system analysis of the properties of business ecosystems is carried out with a subsequent description of the methodology for studying the impact of financial indicators on it. As an example of data for calculation, the article uses Yandex data for 2023, as the most indicative business ecosystem with all the necessary properties. The results of the study allow formulating recommendations for top management on making management decisions and points of application of efforts. Combining the developed methodology with promising technologies for automated calculation of big data and AI will provide a flexible management tool with the possibility of its further development.